When Honesty Breaks the Conversation: Cooperative Principle Violations by an Autistic Doctor in the Good Doctor Season 1 - Ketut Julia Purnama; Ni Putu Cahyani Putri Utami (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
This study aims to investigate how Dr. Shaun Murphy's literal interpretation and characteristic honesty contribute to violations of Grice's Cooperative Principle in The Good Doctor Season 1. A descriptive qualitative method was employed by analyzing conversational utterances collected through observation, note-taking, and transcript analysis across all eighteen episodes. The findings identified 158 instances of Cooperative Principle violations. The Maxim of Relation occurred most frequently with 99 instances, followed by Quantity with 24, Manner with 18, and Quality with 11. In addition, six instances involved combined violations of two maxims. Most violations (134) were unintentional, while 24 were intentional, indicating that Shaun's conversational difficulties primarily result from literal language processing and limited interpretation of implicit meanings rather than deliberate non-cooperation. These findings demonstrate how autistic communication characteristics influence pragmatic interaction and conversational effectiveness. Future studies are encouraged to examine pragmatic communication among autistic characters using broader datasets, different media, or comparative psycholinguistic perspectives.